PENGARUH SEBELUM DAN SESUDAH DILAKUKAN PIJAT LAKTASI TERHADAP PRODUKSI AIR SUSU IBU PADA IBU POSTPARTUM DI BPM MEILISA AFTY DEPOK PERIODE 14 JUNI – 14 JULI 2021 - Nisa, Zakia Hary (Ikatan Bidan Indonesia (IBI), 2023)
Background: breast milk (ASI) is the best food for babies because it contains many nutrients. Data in Indonesia, only 1 in 2 infants under 6 months of age are exclusively breastfed and 38% of mothers stop breastfeeding due to lack of milk production. One method of increasing breast milk production is by lactation massage. The purpose of the study: was to determine the effect of before and after lactation massage on the production of brest milk on postpartum mothers at BPM Meilisa Afty Depok for the period June 14 – July 14, 2021. Methods: This study is an experimental study, with a one-group pre-test and post-test design. The number of samples as many as 35 postpartum mothers with a sampling technique that is purposive sampling. The lactation massage was carried out for 7 days and the measurement of milk production was carried out on the 1st and 7th days. Results: Breast milk production before lactation massage was found to all have less milk production as many as 35 people (100%) and after lactation massage it was found that most of them had sufficient milk production as many as 25 people (71.4%). The results of the Wilcoxon test showed the effect of before and after lactation massage on the production of breast milk on postpartum mothers at BPM Meilisa Afty (p value = 0.000 ≤0.05). Conclusion: the results showed that there was an increase in breast milk production after lactation massage was given. Suggestions: it is hoped that health workers can use lactation massage as a non-pharmacological alternative in an effort to increase breast milk production and educate mothers in the prenatal and postpartum periods regarding breastfeeding.